Donor organ distribution according to urgency of need or outcome maximization in liver transplantation. A questionnaire survey among patients and medical staff. (21st January 2015) - Umgelter, Katrin S.; Tobiasch, Moritz; Anetsberger, Aida; Blobner, Manfred; Thorban, Stefan; Umgelter, Andreas
Summary: Low donor rates in Germany cause a trade‐off between equity in the distribution of chances for survival and efficiency in dead‐donor liver transplantation. Public attitudes concerning the principles that should govern organ allocation are of interest. We performed a questionnaire‐based study among patients and medical staff. 1826 of 2200 questionnaires were returned. 79.2%, 67.1%, and 24.4% patients wanted to accept liver transplantation for themselves if expected 1‐year survival was 80%, 50%, and 20%, respectively. 57.7% affirmed 'averting immediate risk of death (urgency) is a more important criterion for organ allocation than expected long‐term success' ( P  = 0.002 against indifference). The majority of medical staff took the opposite decision. 20.7%, 8.8%, and 21.2% of patients chose 50%, 33%, and 10% as lowest acceptable 5‐year survival, respectively. 49.3% accepted a survival of <10%. Variables associated with preferring urgency over efficiency as criterion for allocation were age (OR 1.009; 95% CI: 1.000–1.017; female gender (OR 1.331; 95%CI 0.992–1.784); higher education (OR 0.881; 95%CI 0.801–0.969); and refusal of transplantation for oneself (OR 1.719; 95%CI 1.272–2.324). Most patients supported urgency‐based liver allocation. Patients and medical staff would accept lower survival rates than the transplant community.